The Politics of Participation in Cultural Policy Making - Lechelt, Elysia; Cunningham, Malaika (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
Recent attempts by local governments to engage in participatory policy-making hint at a willingness for a more democratically inclusive approach to policy. However, there is often a gap between the rhetoric of citizen engagement and the actual implementation of these policy-making initiatives. There is concern that, in certain instances, the terms ‘co-production’ and ‘participatory democracy’ have been adopted whilst the participatory nature of policy-making procedures has, in reality, remained very limited. This article aims to contribute to these broader discussions and debates around the democratic nature of ‘co-produced’ policy practices. This article considers Calgary’s recent ‘co-produced’ Cultural Plan as a potential example of participatory policy-making. Using a framework based on key concepts within the democratic theory, including works by Arnstein (1969), Rawls (1971) and Pateman (1970, 2012), we consider how the strategy adopts participatory policy-making processes, and question how the plan’s development process has succeeded and failed in creating meaningful participation.